Partial Oral Antibiotic Therapy for Infective Endocarditis: A Practical Review of Current Evidence and Guidelines - Thomas Roland; Jean Cyr Yombi (Pathogens, 2026)
Infective endocarditis (IE) is associated with an in-hospital mortality rate of 15–30%. Standard treatment requires 2 to 6 weeks of intravenous (IV) antibiotic therapy, resulting in prolonged hospitalization with its attendant risks, including catheter-related complications, increased length of stay, and cost. This review summarizes the current evidence, eligibility criteria, antibiotic regimen selection, and practical aspects of partial oral antibiotic therapy (POAT) for IE. Oral treatment is already recommended for right-sided Staphylococcus aureus IE and IE caused by selected atypical pathogens (e.g., Brucella spp., Coxiella burnetii, Bartonella spp., and Tropheryma whipplei). The landmark Partial Oral Treatment of Endocarditis trial (2019) demonstrated the non-inferiority of POAT—initiated after at least 10 days of IV therapy—versus continued IV treatment for left-sided IE caused by streptococci, Enterococcus faecalis, S. aureus, or coagulase-negative staphylococci. Long-term follow-up at 5.4 years demonstrated lower all-cause mortality in the POAT group. The 2023 European Society of Cardiology Guidelines now formally endorse POAT for selected patients fulfilling strict criteria. Despite robust evidence, POAT is currently implemented in fewer than half of eligible patients. These findings have since been corroborated by the WikiGuidelines Group consensus statement and the French Société de Pathologie Infectieuse de Langue Française–Association pour l’Étude et la Prévention de l’Endocardite Infectieuse position statement, and extended by real-world evidence (the ENDO-ORAL study) suggesting that carefully selected patients falling outside strict trial-based eligibility criteria may also benefit from oral step-down therapy. In appropriately selected and clinically stable patients, POAT is supported by randomized and real-world evidence as an alternative to prolonged IV therapy. Strict adherence to eligibility criteria, appropriate antibiotic selection based on pathogen susceptibility, and close clinical follow-up are essential to optimize outcomes.